Exhausted signature and regulatory network of NK cells in myasthenia gravis - Zhang, Qing; Han, Xingyu; Bi, Zhuajin; Yang, Mengge; Lin, Jing; Li, Zhijun; Zhang, Min; Bu, Bitao (Frontiers in Immunology, 2024)
NK cells are dysfunctional in myasthenia gravis (MG), but the mechanism is unclear. This study aims to measure associations and underlying mechanisms between the NK cells and the development of MG. Twenty healthy controls (HCs) and 53 MG patients who did not receive glucocorticoids and immunosuppressants were collected. According to the Myasthenia Gravis Foundation of America (MGFA) classification, MG patients were categorized into MGFA I group (n = 18) and MGFA ⅠⅠ-ⅠV group (n = 35). Flow cytometry, cell sorting, ELISA, mRNA-sequencing, RT-qPCR, western blot, and cell culture experiments were performed to evaluate the regulatory mechanism of exhausted NK cells. Peripheral NK cells in MGFA ⅠⅠ-ⅠV patients exhibit exhausted phenotypes than HCs, marked by the dramatic loss of total NK cells, CD56dimCD16− NK cells, elevated PD1 expression, reduced NKG2D expression, impaired cytotoxic activity (perforin, granzyme B, CD107a) and cytokine secretion (IFN-γ). Plasma IL-6 and IL-21 are elevated in MG patients and mainly derived from the aberrant expansion of monocytes and Tfh cells, respectively. IL-6/IL-21 cooperatively induced NK-cell exhausted signature via upregulating SOCS2 and inhibiting the phosphorylation of STAT5. SOCS2 siRNA and IL-2 supplement attenuated the IL-6/IL-21-mediated alteration of NK-cell phenotypes and function. Inhibition of IL-6/IL-21/SOCS2/STAT5 pathway and recovery of NK-cell ability to inhibit autoimmunity may be a new direction in the treatment of MG.